UTILIZATION OF BIOMASS WASTE WITH STEARIC ACID AS FIRE STARTER - Juang, Dejan; Zulfa Arifah, Devinta; Alfaroh, Baiqi; Sabila Rasyad, Alvin; Agustina, Ana (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Fire starter is a product used to ignite a flame, particularly when using firewood, and is considered a potential alternative solution for managing biomass waste in Indonesia. This study aims to determine the quality of fire starters made from sawdust, pine cones, and dry leaves, using stearic acid as an adhesive. The research consists of three stages: production of fire starter, quality testing, and data analysis. The ratios of biomass to stearic acid used in this study are 3:8, 2:7, and 1:6. The quality tests conducted include ignition time, burn duration, burning rate, flame height, and durability test. The results indicate that in the ignition time test, the fire starter made from dry leaves had the fastest ignition time (17 seconds). The burn duration test showed that sawdust was the best material (1,423 seconds). The burning rate test found that dry leaves had the best result (0.035 g/s). The flame height test revealed that sawdust produced the tallest flame (35 cm). For the durability test, all the fire starters had the same durability value (100%).